Comparative study of tramadol and ketorolac in the pain management of third molar tooth extraction - Shaik, MM; Kumar, J; Mobina, S; Satyanarayana, N; Sunitha, P (Journal of College of Medical Sciences-Nepal, 2010)
Objective: Clinical comparison of efficacy, duration of action, onset of action, side effects of two most commonly used analgesics tramadol and ketorolac after the third molar tooth extraction. Materials and methods: The present study was carried out at department of oral surgery, Mamata Dental Hospital, Khammam, India. 150 patients were randomly selected and divided into two groups. Group A received 50 mg of tramadol orally and Group B received 10 mg of ketorolac orally. In both groups dose was repeated for next 24 hrs. Visual scale analog was used for the collection of pain intensity from the patients. Results: In Group A, the analgesia started within 1hour and at the end of 24 hours, pain intensity was 2.12 out of 10 on visual analog scale. In Group B, analgesia started within 30 mins and at the end of 24 hours, the pain intensity was 2.98 on visual analog scale. Sedation associated with dizziness and muscle relaxation was observed with tramadol in 5% of patients and sweating in 8% patients. While in case of ketorolac, 33% of patients suffered with side effects. Among them 33% patients suffered with bleeding at the site of tooth extraction and 20% patients suffered with epigastric pain. The analgesic effect of 50 mg tramadol lasted up to 6 hours and that of ketorolac lasted for 5 hour. Conclusion: The study shows that tramadol is a suitable and safe analgesic for the relief of post-extraction pain and is more effective than ketorolac with prolonged analgesia and minimal side effects. Key Words: Tramadol; ketorolac; third molar tooth extraction DOI: 10.3126/jcmsn.v6i1.3600 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 35-43